2023
DOI: 10.3390/brainsci13030468
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop tACS Delivered during Slow-Wave Sleep Reduces Retroactive Interference on a Paired-Associates Learning Task

Abstract: Previous studies have found a benefit of closed-loop transcranial alternating current stimulation (CL-tACS) matched to ongoing slow-wave oscillations (SWO) during sleep on memory consolidation for words in a paired associates task (PAT). Here, we examined the effects of CL-tACS in a retroactive interference PAT (ri-PAT) paradigm, where additional stimuli were presented to increase interference and reduce memory performance. Thirty-one participants were tested on a PAT before sleep, and CL-tACS was applied over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…This demonstrates the generalizability of our approach in stimulation protocol design for other types of stimulation methods, beyond tACS. In addition to sinusoidal and square waveforms, which are common brain stimulation signals in literature ( Marshall et al, 2011 ; Bueno-Lopez et al, 2019 ; Fehér et al, 2021 ; Jones et al, 2023 ), we examine signals of higher complexity, including sum of sinusoidal waveforms and polynomial waveforms, which can be easily generated through Arbitrary Waveform Generators, allowing users to tailor spectral or temporal properties of the signal ( Baig et al, 2013 ). Our analysis also showed that the accuracy of the stimulation protocol depended on △ t values, and that there was at least one condition (square waveform, △ t 100ms and stage 2 sleep) in which our algorithm could not design a stimulation protocol that targeted global SOs at all, at least within the chosen (and very broad) parameter search regions.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the generalizability of our approach in stimulation protocol design for other types of stimulation methods, beyond tACS. In addition to sinusoidal and square waveforms, which are common brain stimulation signals in literature ( Marshall et al, 2011 ; Bueno-Lopez et al, 2019 ; Fehér et al, 2021 ; Jones et al, 2023 ), we examine signals of higher complexity, including sum of sinusoidal waveforms and polynomial waveforms, which can be easily generated through Arbitrary Waveform Generators, allowing users to tailor spectral or temporal properties of the signal ( Baig et al, 2013 ). Our analysis also showed that the accuracy of the stimulation protocol depended on △ t values, and that there was at least one condition (square waveform, △ t 100ms and stage 2 sleep) in which our algorithm could not design a stimulation protocol that targeted global SOs at all, at least within the chosen (and very broad) parameter search regions.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the generalizability of our approach in stimulation protocol design for other types of stimulation methods, beyond tACS. In addition to sinusoidal and square waveforms, which are common brain stimulation signals in literature [67][68][69][70], we examine signals of higher complexity, including sum of sinusoidal waveforms and polynomial waveforms, which can be easily generated through Arbitrary Waveform Generators, allowing users to tailor spectral or temporal properties of the signal [71]. Our analysis also showed that the accuracy of the stimulation protocol depended on ‫ݐ∆‬ values, and that there was at least one condition (square waveform, ‫ݐ∆‬ 100ms and stage 2 sleep) in which our algorithm could not design a stimulation protocol that targeted global SOs at all, at least within the chosen (and very broad) parameter search regions.…”
Section: Discussionmentioning
confidence: 99%